Interview: A Visit with Richard Epstein. - Snoonian, Deborah (Architectural Record, 2003)
This article presents an interview with architect Richard Epstein who has his own firm in Boulder, Colorado, since 1992 and has designed a variety of commercial, residential, and mixed-use projects. Public art and sustainability have been the mainstays of his practice. His firm is basically a PC office, and for design, the firm primarily uses AutoCAD and Form-Z. The firm has explored to some degree the idea of parametric modeling, using some software packages.